2012
DOI: 10.32635/2176-9745.rbc.2012v58n3.591
|View full text |Cite
|
Sign up to set email alerts
|

Câncer do Colo do Útero no Estado de Mato Grosso do Sul: Detecção Precoce, Incidência e Mortalidade

Abstract: Introdução: O câncer do colo do útero apresenta taxas de incidência e mortalidade elevadas no Brasil. Objetivo: Descrever a cobertura das ações de detecção precoce do câncer do colo do útero, sua incidência e mortalidade no Estado de Mato Grosso do Sul. Método: Estudo descritivo e exploratório. Foram analisados dados provenientes do Departamento de Informática do SUS , Instituto Brasileiro de Geografia e Estatística, Instituto Nacional de Câncer José Alencar Gomes da Silva. Foi realizada análise descritiva das… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
2
0
2
Order By: Relevance
“…A study that analyzed cervical cancer incidence and mortality in the state of Mato Grosso do Sul reported an increase of 139% in the incidence rate between 2001 and 2012, and growth of around 30% in age-adjusted mortality rates between 1979 and 2009. 7 In that study, cervical cancer mortality rates were reported in the municipality of Campo Grande that ranged from 5.13 to 10.2/100,000 women between 1980 and 2009. 7 In 2020, 270 new cases and an age-adjusted incidence rate of 18.3/100,000 women were estimated for the state of Mato Grosso do Sul as a whole, while 40 new cases and an age-adjusted incidence rate of 8.1/100,000 women were estimated for the state capital, Campo Grande.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…A study that analyzed cervical cancer incidence and mortality in the state of Mato Grosso do Sul reported an increase of 139% in the incidence rate between 2001 and 2012, and growth of around 30% in age-adjusted mortality rates between 1979 and 2009. 7 In that study, cervical cancer mortality rates were reported in the municipality of Campo Grande that ranged from 5.13 to 10.2/100,000 women between 1980 and 2009. 7 In 2020, 270 new cases and an age-adjusted incidence rate of 18.3/100,000 women were estimated for the state of Mato Grosso do Sul as a whole, while 40 new cases and an age-adjusted incidence rate of 8.1/100,000 women were estimated for the state capital, Campo Grande.…”
Section: Introductionmentioning
confidence: 95%
“… 7 In that study, cervical cancer mortality rates were reported in the municipality of Campo Grande that ranged from 5.13 to 10.2/100,000 women between 1980 and 2009. 7 In 2020, 270 new cases and an age-adjusted incidence rate of 18.3/100,000 women were estimated for the state of Mato Grosso do Sul as a whole, while 40 new cases and an age-adjusted incidence rate of 8.1/100,000 women were estimated for the state capital, Campo Grande. 8 These data point to the importance of evaluating the actions of Campo Grande's Cervical Cancer Control Program ( Programa de Controle do Câncer do Colo do Útero - CCPCU), to contribute to the development of screening actions contribute to the development of screening actions aimed at reducing cervical cancer incidence and mortality rates.…”
Section: Introductionmentioning
confidence: 95%
“…20 Ficou evidenciado nesta revisão de literatura que a tendência temporal da incidência e mortalidade de câncer cervical pode estar diretamente relacionada à exposição da população feminina a fatores de risco, tais como o início precoce da atividade sexual, múltiplos parceiros sexuais, uso de anticoncepcionais, tabagismo, alta paridade, bem como acesso a oferta de programas de rastreamento universal e de qualidade e à rede de atenção oncológica para tratamento oportuno da doença. 2, [40][41] Adicionalmente, localidades com condições socioeconômicas desfavoráveis apresentam maiores taxas de mortalidade por câncer cervical. [42][43][44] Desta forma, a melhoria nos indicadores socioeconômicos e investimentos na atenção primária à saúde estão intrinsecamente ligados à redução das taxas de mortalidade.…”
Section: Mortalidade Por Câncer Cervical No Brasilunclassified
“…Nesse contexto, o objetivo deste artigo foi descrever o panorama epidemiológico dos casos de câncer de colo de útero no Acre entre os anos de 2015 e 2020. ScientiaNaturalis, Rio Branco, v. 4, n. 1, p. 186-197, 2022 p. 188 informações, reunindo dados acerca de identificação de mulheres, informações epidemiológicas, demográficas, laudos dos exames histopatológicos, citológicos e uma área de monitoramento do processo de mulheres que apresentaram lesões précancerígenas (FREITAS et al, 2012).…”
Section: Introductionunclassified